(untitled) (Borneo Engineering & Advanced Multidisciplinary International Journal, 2023)
Understanding students' perspectives on online learning platforms is essential in the current educational environment. This study explores the satisfaction of Communicative English students at a Politeknik Mukah on course content uploaded on LMS during the pandemic. The survey is administered to 100 fourth-term students enrolled in "Communicative English 3," comprising 30% from the engineering field and 70% from non-engineering field. The reliability of the questionnaire indicates good internal consistency with Cronbach Alpha of 0.961. The outcome reveals that understanding the perceptions of students and the impact of course content can enhance online learning experiences, increase students’ engagement, and increase satisfaction. The findings can aid educators, institutions, and policymakers in making well-informed decisions to improve online education and acclimatize to the changing educational landscape.